Women in the world of work: choosing the "male" course and entering the internship (Research, Society and Development, 2021)
The choice of women to study in a course in a traditionally male area (Occupational Safety) and their inclusion in the internship are the theme of this work, written from a survey that was carried out in the school environment of the Federal Institute of Alagoas (IFAL) – São Miguel dos Campos Campus. Its objective is to understand the socio-historical-emotional aspects that involve this choice and to get to know the reality of women when performing the internship, a crucial step for the consolidation of the course's teachings and for their employability. The research also aims to broaden the debate at IFAL, focusing on issues of gender, education and work. The investigative study is characterized as an action-research, with a quanti-qualitative nature, and the methodological instruments used were the semi-structured questionnaire and the conversation wheel. The data point to the need to expand research involving gender and EPT, in order to think of education as a promoter of critical thinking, to stimulate discussions and practices that strengthen gender equity, in IFAL and in society.